SISTEM PENDUKUNG KEPUTUSAN PENYEWAAN KOS-KOSAN DI DESA ANJANI MENGUNAKAN METODE SIMPLE ADAPTING WEIGHTING (SAW) BERBASIS WEB - Zulkarnaen, Zulkarnaen; Antarul Aziz (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
The existence of boarding houses around public facilities is very desirable and beneficial for students who come from outside the area to study at university. However, the many choices of boarding houses with different prices, facilities and distances make students confused when choosing a temporary place to live. To overcome this problem, the web-based Simple Additive Weighting (SAW) method is used in a decision support system. This system provides recommendations or suggestions for boarding houses that match the criteria entered by the user. The user will input criteria and alternatives into the system, then the system will carry out a calculation process to provide a list of recommended boarding places. The research results show that this system can help prospective boarding house renters in choosing recommended alternative boarding places based on criteria and user input using the SAW method. With this system, students can more easily find temporary housing that suits their needs.